If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
13 = (2*x)/3 // - (2*x)/3
13-((2*x)/3) = 0
(-2/3)*x+13 = 0
13-2/3*x = 0 // - 13
-2/3*x = -13 // : -2/3
x = -13/(-2/3)
x = 39/2
x = 39/2
| 15+13x+2=180 | | 7x+9x-8x-5=51 | | 6+5[7n-7]=6 | | X^2-x/x-1=3 | | 32y^2=392 | | 9x+x+x=44 | | 5n^2-75n=0 | | -25=-24d-d^2 | | 6y+40=3y-14 | | -35+4x+3x=35 | | -3[-6a+2]-1=-61 | | 80=2(3.14)(4)k | | 3x+7+2x=52 | | 0=13-7lnx | | 33x-33=33x+25 | | -200=b+(73) | | 6m^2-52m-18=0 | | cos(x)=4-x^2 | | 10d^2-270d=0 | | T/12=225/15 | | 33x-25=33x+25 | | 12-(-z)=17 | | 30u=-2u^2 | | 3x^2-4x-4y=0 | | 8x+42-2x=1x | | 289t^2-1=0 | | 9/12=m/17 | | 5x+3x=2x | | 150=c | | (13-x)/4=5 | | 4z^2+36z+81=0 | | y-12=62 |